TRADISI POLITIK DAN CAKRAWALA BARU DALAM PERADABAN YANG MUNCUL PADA MASA PRESTISE MONGOL - Isna Juwita Sari isna; Eka Lazuardi; Rumi Magistra Pama Rumi (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2025)
The Mongol Prestige Period (13th to 14th centuries) was a period of great transformation in world politics and civilization. Under the leadership of Genghis Khan and his successors, the Mongol Empire and their dominance over various civilizations. the Mongol rule not only expanded its territory, but also established an innovative political system by adapting elements of the various cultures they conquered. In addition, the stability they created through Pax Mongolica, a vast trade network flourishing, allowed for the exchange of science, technology, and political ideology between East and West. This blend of political innovation and cultural interaction formed a new attraction in global civilization, influencing various kingdoms and countries later on. This article analyzes the influence of Mongol political traditions on the structure of government and how the inter-civilizational interactions of the time shaped the modern world. The political traditions developed by the Mongol empire had a long-term impact on the system of government in various regions, including the implementation of meritocratic systems, the centralization of government, as well as the policies of religious tolerance implemented in various post-Mongol empires such as the Ming Dynasty in China, the Ottoman Empire, and the Russian empire. The new horizons that opened up through cultural interaction and trade also accelerated the advancement of science in Europe and the Islamic world, which helped to the birth.